North Kosovo and the Serbia-Kosovo Normalization Dialogue - Gustavo Oliveira Teles de Menezes (Političke Perspektive, 2020)
The article describes and discusses political and security trends in Serb-majority North Kosovo during the Serbia-Kosovo normalization process launched in 2011. Perspectives from the local Serb population in the face of the interests and policies of the governments of Serbia, Kosovo and the Western great powers that promote normalization are highlighted, showing that critical views of normalization and associated trends are widespread in North Kosovo. In this connection, it is argued that dissatisfaction and insecurity with normalization and associated trends also became present in the region’s political life, pointing to latent challenges to the legitimacy and sustainability of normalization.